Surgical simulation flexor tendon repair using Thiel cadavers: a comparison with formalin embalmed cadavers and porcine models. (March 2015) - Hassan, S.; Eisma, R.; Malhas, A.; Soames, R.; Harry, L.
The aim of this study was to compare Thiel-embalmed cadavers with formalin-embalmed cadavers and porcine models in the surgical simulation repair of a Zone II flexor tendon division. Nine participants were recruited to the study. The models were assessed using a five-point scale. Assessment was divided into tissue quality, surgical approach and identification of structures. Thiel cadavers rated consistently higher compared with the formalin and porcine models (mean 37 SD 2, 22 SD 6 and 23 SD 5, respectively). Thiel cadavers recorded an average tendon glide of 21 mm SD 5, formalin cadavers 2 mm SD 2 and the porcine model 6 mm SD 2. We have demonstrated the benefit of Thiel embalming, with flexibility of tissues allowing testing of the repair of a flexor tendon in a realistic anatomical model. Level of evidence: Level V.